Generation of 12 W 257 nm laser pulses by sum-frequency generation based on LBO crystals. (1st August 2022) - Cha, Yong-Ho; Kim, Suwon; Park, Hyunmin
Abstract: We have generated high-power deep ultraviolet laser pulses from a Yb-doped rod-type fiber laser through sum-frequency generation (SFG) based on lithium triborate (LBO) crystals. The 1030 nm nanosecond laser pulses from the fiber laser are frequency-tripled to 343 nm pulses with two LBO crystals, and the residual 1030 nm fundamental laser pulses are mixed with the 343 nm pulses in an LBO crystal for the generation of 257 nm pulses. The maximum 257 nm radiation power is 12 W with a repetition rate of 500 kHz, and the conversion efficiency from 1030 nm to 257 nm is 12%. It is observed that the power of 257 nm radiation is limited by the temperature increase in the LBO crystal used for the SFG.